Comparison of Recurrence Rate of Pterygium Following Excision by Bare Sclera Technique with and without Conjunctival Autograft – A Hospital-based Study - Rafiq, Khurram; Muneer, Madasar; Khan, Waseem Ahmed (Biological and Clinical Sciences Research Journal, 2025)
Pterygium is a common ocular surface disorder in Pakistan, driven by high ultraviolet exposure and environmental irritants. Recurrence following surgical excision remains a major clinical challenge. While the bare sclera technique is widely performed due to its simplicity, conjunctival autografting has been proposed to reduce recurrence. This study compared postoperative recurrence between bare sclera excision and conjunctival autografting. Methods: A randomized controlled trial was conducted at the Ophthalmology Department of Ibn-e-Sina Hospital in Multan from September 2024 to February 2025. One hundred and twenty-eight patients aged 15–65 years with primary pterygium were enrolled through consecutive sampling. Participants were randomized into two equal groups: Group A underwent pterygium excision using the bare sclera technique, while Group B underwent excision followed by conjunctival autograft placement. Patients were evaluated clinically at 1 day, 1 week, and monthly for six months. Recurrence was defined as fibrovascular regrowth across the limbus. Data were analyzed with SPSS version 23, using chi-square and independent t-tests, with p ≤ 0.05 considered statistically significant. Results: The mean age was 42.6 ± 11.3 years, and females constituted 54.7% of the cohort. Most participants (64.1%) had symptoms for 3–6 months. Recurrence was significantly higher in the bare sclera group (21.9%) than in the autograft group (12.5%). No statistically significant relationship was observed between recurrence and patient age (p = 0.21), gender (p = 0.63), or symptom duration (p = 0.12). Thus, the surgical method was the primary determinant of the recurrence rate. Conclusion: Conjunctival autografting was superior to the bare sclera technique in reducing the recurrence of pterygium following excision. These findings reinforce the need to adopt autograft-based approaches in high-risk settings such as Pakistan to improve patient outcomes and minimize repeat surgery.